2020
DOI: 10.1111/1759-7714.13661
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of pretreatment smoking status for small cell lung cancer: A meta‐analysis

Abstract: Background Although tobacco exposure remains the most important risk factor of tumorigenesis of small cell lung cancer (SCLC), its prognostic value has failed to reach a consensus until now. Accordingly, we conducted a meta‐analysis to investigate the prognostic value of pretreatment smoking status (smokers vs. never‐smokers) in SCLC. Methods The four databases PubMed, Medline, Embase, and Cochrane library were searched to identify the relevant literature from the incep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…In non-small cell lung cancer, the incidence of the driver mutation accounts for the survival difference between male and female patients; in SCLC, this may be explained by the prevalence of smoking. A previous meta-analysis has shown that smoking history was closely related to poorer survival outcomes [ 13 ]. Despite smoking status being largely missing in the present analysis, we assumed that the survival difference based on sex could be related to the divergence of smoking status between men and women.…”
Section: Discussionmentioning
confidence: 99%
“…In non-small cell lung cancer, the incidence of the driver mutation accounts for the survival difference between male and female patients; in SCLC, this may be explained by the prevalence of smoking. A previous meta-analysis has shown that smoking history was closely related to poorer survival outcomes [ 13 ]. Despite smoking status being largely missing in the present analysis, we assumed that the survival difference based on sex could be related to the divergence of smoking status between men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is associated with a poorer prognosis in patients with small-/non-small cell lung cancer (SCLC/NSCLC) and breast cancer [27][28][29]. Regarding hypercholesterolemia, cholesterol-lowering medication was associated with a decrease in cancer mortality in in a large meta-analysis of breast cancer patients [30].…”
Section: Introductionmentioning
confidence: 99%
“…Tedavi öncesi sigara içmek, genomik profil, dolaşan tümör hücreleri, Geriatric Nutritional Risk Index, delta-like protein 3 ve serum laktat dehidrogenaz seviyeleri bildirilmiş prognostik faktörlerdendir. [3][4][5][6][7][8] Kanser gelişimi ve progresyonunda inflamasyon hücreleri ve kemokinler önemli temel prognostik belirteçlerdir. 9 Lenfositler doğal immünitenin bir parçası olarak sitotoksik hücre ölümünü tetiklemektelerdir.…”
Section: Introductionunclassified